2013
DOI: 10.1021/ic400019r
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antitumor Agent, Trilacunary Keggin-Type Tungstobismuthate, Inhibits Proliferation and Induces Apoptosis in Human Gastric Cancer SGC-7901 Cells

Abstract: A new one-dimensional chain-like compound of tungstobismuthate, [(W(OH)2)2 (Mn(H2O)3)2(Na3(H2O)14)(BiW9O33)2](Himi)2·16H2O (1) (imi = iminazole), has been synthesized in aqueous solution. The structure of 1 was identified by elemental analysis, IR, thermogravimetry (TG), X-ray photoelectron spectroscopy (XPS), (183)W-NMR, and single crystal X-ray diffraction. To investigate the inhibitory effect of 1 on human gastric adenocarcinoma SGC-7901 cells, cell proliferation and apoptosis initiation were examined by MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 96 publications
0
42
0
Order By: Relevance
“…With the development of POM and modified chemistry, POM could be covalently linked with the organic groups or biological macromolecules, which have the targeting recognition on human body, resulting in changes of POM surface charge distribution to enhance the target recognition and drug activities . Isopoly Mo series modified by orgnaophosphorus could inhibit the growth of lung cancer NCI‐H460 cells, breast cancer MCF‐7 cells, and nervous central cancer SF‐268 cells, leading to being interested by many researchers . In our previous studies, the two Krebs of Keggin‐type imidazole‐modified polyoxotungstates were synthesized, which exhibited a conspicuously inhibitory growth and induction apoptosis in human gastric cancer SGC‐7901 cells and colon cancer HT29 cells .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of POM and modified chemistry, POM could be covalently linked with the organic groups or biological macromolecules, which have the targeting recognition on human body, resulting in changes of POM surface charge distribution to enhance the target recognition and drug activities . Isopoly Mo series modified by orgnaophosphorus could inhibit the growth of lung cancer NCI‐H460 cells, breast cancer MCF‐7 cells, and nervous central cancer SF‐268 cells, leading to being interested by many researchers . In our previous studies, the two Krebs of Keggin‐type imidazole‐modified polyoxotungstates were synthesized, which exhibited a conspicuously inhibitory growth and induction apoptosis in human gastric cancer SGC‐7901 cells and colon cancer HT29 cells .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A lot of achievements at the molecular level have been gained, in which several factors such as the size, shape, and nature of the embedded metal ion in the architecture of POM are demonstrated to be crucial in governing the interactions. 13 10 O 36 ] 9− ) and bovine serum albumin (BSA) with a moderate association constant, 13 they found that the complicated structure of the selected POM had a significantly higher affinity to the proteins than the simple one. 14 20,21 In the following, Goovaerts et al calculated the association constants of several Keggin-type POMs with BSA and HSA, and pointed out the binding site at the surface of albumins.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are metal–oxygen cluster species with a diverse compositional range and an enormous structural variety, which exhibit interesting and exciting properties . As a consequence, potential applications of POMs span a wide range of fields including catalysis, electrocatalysis, photocatalysis, medicine, materials science, photochemistry, biochemistry, analytical chemistry, magnetochemistry, etc.…”
Section: Introductionmentioning
confidence: 99%